2022
DOI: 10.3390/healthcare10030424
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Studies of Different Cancer Diseases among Less-Developed Countries

Abstract: Recently, the rate of cancer deaths in less-developed countries such as Bangladesh has significantly increased day by day, making it a major health issue. The most predominant types of cancers among the populations of less-developed countries (especially Bangladesh) are lung, throat, colon, gastric, ovarian, breast, and skin cancers. The mortality rate is increasing for both males and females. The main common factors are smoking, use of tobacco leaves, bacterial or viral infection, hereditary disorders, food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Every year, more people die from cancer than other chronic diseases, such as HIV, malaria, and tuberculosis combined. In 2020, the death rate was close to 55%, compared to nearly 25% in 1960 [ 31 ]. Several genes are typically involved in carcinoma development through the deregulation of cellular growth, nucleic acid repair, chromosome instability, cell interaction and communication, angiogenesis, and changes in the apoptotic pathway [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every year, more people die from cancer than other chronic diseases, such as HIV, malaria, and tuberculosis combined. In 2020, the death rate was close to 55%, compared to nearly 25% in 1960 [ 31 ]. Several genes are typically involved in carcinoma development through the deregulation of cellular growth, nucleic acid repair, chromosome instability, cell interaction and communication, angiogenesis, and changes in the apoptotic pathway [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The compounds were selected based on the docking score and the toxicity class. Current third-generation inhibitors, osimertinib, belong to class 3 (LD 50 :100 mg/kg) with active immunotoxicity, and first-generation gefitinib belongs to class 5 (LD 50 :2935 mg/kg); both are being widely used as TK inhibitors in Asia ( Rahman et al, 2022 ). These drugs also have hepatotoxicity and immunotoxicity and are active in binding aryl hydrocarbon receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR family consists of four different subgroups: erbB1, erbB2, erbB3, and erbB4 ( Bethune et al, 2010 ). Mutation in this group of genes shows the development of several cancers in humans, such as lung cancer, colorectal cancer, breast cancer, liver cancer, pancreatic cancer, and ovarian cancer ( Krasinskas 2011 ; Rahman et al, 2022 ). The most common cancer is non-small-cell lung cancer caused by mutation of EGFR in exon 19 and L858R positions ( Yan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is no published data about the incidence of APL from either of the two countries; however chemical exposure and dietary factors had been reported from Bangladesh as a possible underlying cause of cancer [14,15]. A study on commonest cancer in Yemen, showed leukemia was the highest in males and it came next to breast cancer in females (no mention of the type of leukemia whether acute, chronic, myeloid, or lymphoid) [16].…”
Section: Discussionmentioning
confidence: 99%